Dynamic evolution control for synchronous buck DC-DC converter: Theory, model and simulation - Samosir, Ahmad Saudi (Elsevier B.V., 2010)
This paper proposes a new control technique for synchronous buck DC-DC converter. Theory, design and implementation of the proposed control technique are provided. A new approach for converter controller synthesis based on dynamic evolution control theory is presented. In order to synthesize the converter controller, this method uses a simple analysis of nonlinear equation models of the converter. The synthesis process is simple and requires a quite low bandwidth for the controller. Therefore, this control method is suitable for digital control implementation. As an illustrative example, the synthesis of synchronous buck DC-DC converter controller is discussed in detail. The model of the synchronous buck DC-DC converter system was implemented using SimPowerSystems toolbox of MATLAB-SIMULINK. Performance of the proposed dynamic evolution control under step load change and step input voltage condition was investigated. Simulation results confirm that the proposed control method is superior to traditional PI based controller because of fast transient response and good disturbance rejection.